MEMS-Based Terahertz Detectors. (2015) - Bilgin, H.; Yalcinkaya, A.D.; Torun, H.
Abstract: A MEMS based novel THz detector structure is designed and realized by micro fabrication. The detector is then characterized to extract its mechanical performance. Operating in 1-5 THz band, the detector has a pixel size of 200 μm × 200 μm. Bimaterial suspension legs consist of Parylene-C and titanium, the pair of which provides a high mismatch in coefficients of thermal expansion. The pixel is a suspended Parylene-C structure having a 200 nm-thick titanium metallization. Operation principle relies on conversion of absorbed THz radiation into heat energy on the pixel. This increases the temperature of the free-standing microstructure that is thermally isolated from the substrate. The increase in temperature induces mechanical deflection due to bimaterial springs. The detector is designed to deliver a noise equivalent temperature difference (NETD) less than 500 mK and a refresh rate of 30 Hz.